Epidemiological factors of smallpox and monkeypox in relation to the tradition «The nun with the key» - Palacios Flores, Carlos Augusto (2023)
This article will explain how the pathology of smallpox manifests itself, taking as a reference one of the first reports of smallpox in Peruvian society: the tradition «La monja de la llave» (The Nun with the Key). This narrative image will then be complemented with data from historical sources, which explain the clinical issue and the eradication with the use of vaccines. Some considerations about monkeypox and the growth of cases in Peru today will also be presented. The aim is to raise public awareness and achieve effective prevention of this disease.